Análise da expressão das proteínas P16INK4a, KI67 e MCM7 e da infecção pelo papilomavírus humano (HPV) na progressão das lesões escamosas intraepiteliais do colo uterino - Soraya Lobato (2011)
Cervical cancer is the second most common type of neoplasia, among women from different parts from the world. There is epidemiological evidence that, persistent infection of the cervix with oncogenic types of human papillomavirus (HPV) plays a preponderate role in the development of uterine cervical carcinoma. Since the Papanicolaou (Pap test) cytological screening for cervical precancerous lesions was introduced in the last 30 years, there has been a significant reduction in the incidence and mortality from cervical cancer. However, the efficacy of the Pap test is hampered by high inter-observer variability and high false negative and false positive rates. Even the histological assessment of cervical biopsies that is often considered as the gold standard, can be significantly hampered by intra- and inter-observer variability. Research nowadays is focused on the development of objective biomarkers thatcan distinguish transforming from productive HPV infections and predict disease severity. The cellular tumor suppressor protein p16 INK4a is functionally able to block the activity of cyclin-dependent kinases CDK4/6 and interrupt the progression of the cell cycle. A higher expression of p16 INK4a has been identified as a biomarker for transforming HPV infections. Several studies have found that p16 INK4a is typically over expressed in the dysplasic epithelium. In addition, the high-grade scamous intraepithelial lesions (SILs) exhibit a strong and diffuse labeling for this cell cycle regulating protein. The Ki-67 antigen has been also considered by several studies, as a relevant biomarker for cell proliferation in numerous types of human tumors, including the cervical cancer. The Minichromosome Maintenance (MCM) proteins, which are replicating factors functionally involved in regulating the DNA replicationinitiation, have also been evaluated as proliferating markers in human tissues and cells. In the present study, the expression patterns of p16INK4a, Ki-67 and MCM7 proteins were evaluated in cervical tissue samples, to investigate the usefulness of these molecules as biomarkers for the progression of cervical intraepithelial lesions and for the occurrence of HPV infection. By means of a microscopy scanning - based on Indirect Immunofluorescence approach, the three biomarkers pattern expression was ascertained in cervical tissue samples withouthistopathological alterations, as in those presenting distinct grades of Cervical Intraepithelial Neoplasia (CIN). A complete absence of p16INK4a labeling was observed in the normal cervical epithelium, whilst a significant increase of the protein expression was detected according the severity of the cervical lesions. In addition, a positive correlation between the p16INK4a expression and the presence of HPV DNA was observed. Concerning the Ki-67 expression pattern through the cervical epithelium, it was also verified a significant correlation between the antigen expression and the severity grades of the intraepithelial lesions. However, it has not been observed any correlation between the Ki-67 expression and the HPV infection. Regarding the MCM7 expression in the cervical epithelium, it was verified a significant correlation between the protein labeling and the CIN grading, as well as the presence of HPV infection. By means of the comparison among the expression patternpresented by all the three analyzed biomarkers, it was verified a positive and significant correlation between the MCM7 expression and those corresponding to the two other markers, p16INK4a and Ki-67. Finally, when a comparative analysis was performed, between the expressions of the two proliferation markers through the cervical epithelium, a higher value of MCM7 LI (Labeling index) was observed in all the categories of the cervix epithelium. Based on the findings resulting from this study, it can be concluded that, p16INK4a and MCM7 can be considered valuable biomarkers and useful tools for discriminating between distinct andsevere stages of the progressive cervical disease, and for detecting the associated presence of the HPV infection.